PENGARUH KOMBINASI SARI KACANG HIJAU DAN PISANG AMBON TERHADAP KADAR HEMOGLOBIN IBU HAMIL ANEMIA DI PUSKESMAS RAWASARI KOTA JAMBI - Suryani, Suryani; Murtiyarini, Ika; Sutarty, Tri; Kusmaryani, Pauline (NHM PRESS, 2024)
The Jambi City Health Service in 2022 reported that out of 1047 the number of anemic pregnant women in Jambi City was the highest at the Putri Ayu Health Center with 138 (13.1%) pregnant women, followed by the Kenali Besar Health Center with 115 (10.9%) pregnant women, and the Rawasari Health Center with 115 (10.9%) pregnant women. 55 (5.3%) pregnant women were anemic. This research is a pre-experimental study with a one group pretest posttest design which aims to determine the effect of a combination of green bean juice and Ambon banana on the hemoglobin levels of anemic pregnant women at the Rawasari Community Health Center, Jambi City in 2024. The population in this study were all anemic pregnant women who visited the In the Rawasari Health Center, Jambi City, from March to April 2024 there were 32 pregnant women. Samples were taken by total sampling. This research was conducted from March to July 2024. Data analysis was carried out univariately and bivariately using the t test. Research results The average hemoglobin level before being given a combination of green bean juice and Ambon banana was 9,975 g% and after the intervention it increased to 10,919 g%. The results of the analysis show the effect of a combination of green bean juice and Ambon banana on the hemoglobin levels of anemic pregnant women at the Rawasari Community Health Center, Jambi City in 2024, obtained ρ-value = 0.000 (ρ < 0.05). The combination of green bean juice and Ambon banana can increase the hemoglobin levels of anemic pregnant women. It is hoped that the Community Health Center will apply it to ANC services and provide knowledge to pregnant women about how to increase the hemoglobin levels of anemic pregnant women, namely with non-pharmacological treatment by administering a combination of green bean juice and Ambon banana.